Mua’llagat An-Nabeghah: A Representative of a Mighty Language - Yahya Dahami (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2026)
This study presents an analytical, critical, and descriptive investigation of selected verses from the distinguished poem of An-Nabeghah Ath-Thubyani, which critics consider one of Mu'allaqat (the seven/ten pre-Islamic Arabic odes). The study attempts to highlight the impact of the poet's distinctive characteristics on the prolific nature of his contributions to Arabic poetry. It also seeks to reveal the influence of Arabic poetry on An-Nabeghah Ath-Thubyani, presenting his talent and mastery through two selected verses from his Mu'allaqah. The study is divided into four parts. It begins with a brief overview of the status of the Arabic language and its interaction with Arabic poetry. The next part focuses on the poet himself. It is followed by a descriptive analysis of the selected verses from his Mu'allaqah. The final part consists of the conclusion and recommendations. تُقدّم هذه الدراسة البحثية تقصياً تحليلياً، نقدياً وصفيًا لبعض أبيات قصيدة النابغة الذبياني المتميزة، التي عدّها النقاد من المعلقات. وتحاول الدراسة تسليط الضوء على أثر سمات الشاعر المميزة على غزارة إسهاماته في الشعر العربي. كما تسعى إلى كشف أثر الشعر العربي، مُسلّطةً الضوء على مواهة وملكة النابغة الذبياني من خلال البيتين المختارين من معلقته. تنقسم الدراسة الى أربعة أجزاء رئيسية. تبدأ بلمحة موجزة عن مكانة اللغة العربية وتفاعلها مع الشعر العربي. ثم تنتقل إلى الجزء التالي الذي يُسلّط الضوء على الشاعر. يليه تحليل وصفي لأبيات مختارة من المعلقة. أما الجزء الأخير فهو الخاتمة والتوصيات.